SARAMAGO'S PHİLOSOPHİCAL NARRATİVE - Salman Aliyev; Flora Mirzayeva (European Research Materials, 2024)
This study explores the integration of political philosophy in the novels of José Saramago, a writer deeply influenced by his experiences under Portugal's authoritarian Salazar regime. Saramago's works, characterized by their defiance of religious and state authorities, do not offer straightforward historical or social narratives. Instead, they weave extraordinary tales that incorporate historical and societal elements, blending past, present, and future into narratives that often resemble fairy tales. This blending of temporal segments creates a form of magical realism that is inherently political. Although Saramago was not a political philosopher, his novels embody concepts such as human nature, authority, and legitimacy. These concepts, though not explicitly named, become silent yet real protagonists in his works. Through his masterful storytelling, Saramago transforms these abstract ideas into tangible elements, making his novels profound commentaries on societal and political structures.